Dough rheology and the impact of zinc sulfate on the quality of cookies - USMAN,Muhammad (2021)
Abstract Zinc deficiency is a growing issue in developing countries. Moreover, it is a well-known fact that the bakery products have very low zinc content and the further loss of zinc occurs during milling of wheat and under baking of end products, which makes it hard to produce nutritional bakery products. For this purpose, zinc sulfate has been incorporated in wheat flour at 0, 32.5, 65, and 97.5 mg/100 g to prepare cookies and determine their physicochemical and nutritional properties as well as stability under controlled storage conditions, i.e. temperature (23-25 °C) and relative humidity (45-55%). The findings exhibited that the cookies-percentage of fat and protein decreased after the addition of zinc sulfate. The fiber content of cookies was non-significantly changed, while the moisture content increased. Moreover, the diameter of cookies significantly increased from 45.65 ± 1.46 cm to 45.84 ± 1.34 cm. The thickness and spread factor of cookies were also effects ranged from 1.49 to 1.54 cm and 30.63 ± 2.98 to 29.76 ± 1.64 respectively. The results revealed that zinc sulfate was stable up to 90 days and under normal baking conditions. Based on the sensorial attributes, it was unveiled that the nutritional cookies were prepared by using 65 mg zinc sulfate with (AARI-2011) wheat flour.